Why did Britain's households get richer? Decomposing UK household income growth between 1968 and 2008-09 - Mike Brewer; Liam Wren-Lewis (University of Essex, Institute for Social and Economic Research (ISER), 2012)
Average real UK household income has almost doubled over the past forty years. With four decades of micro-data on household incomes, and relatively simple decomposition methods, we document the contribution to this growth in the mean net household income of working-age households from different income sources, and break down further changes in employment income by household member and into separate participation, hours and hourly wage effects. We also perform such analyses for the mean income of the richest working-age households, and among a group defined by having a low household income but a strong connection to the labour market.
Keywords: D31; E24; 330; income distribution; employment; wages